1974
DOI: 10.1088/0031-9155/19/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Mixed field dosimetry with CaSO4:Dy

Abstract: The thermal neutron response and gamma -ray sensitivity of CaSO4:Dy as a function of Dy concentration were studied in detail. CaSO4 with 0.2% Dy has maximum gamma -ray sensitivity. The thermal neutron response of CaSO4:Dy increases rapidly with concentration beyond 0.1% Dy. CaSO4:0.05% Dy (or Tm) has high gamma -ray sensitivity coupled with low thermal neutron response and hence is useful for gamma -ray dosimetry in mixed fields. A mixture of LiF TLD-100 and TLD-700 was arrived at for rem equivalent dosimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…Our earlier studies [16] have shown that the TL response of the dosimetric peak at 200 "C in LiF TLD-100 is about 30 times more sensitive to thermal neutrons as compared to y-rays on a DE basis. Thus the PL from F t centers in TLD-100 will be nearly 45 times more efficient than that of TL of the 200 "C peak from the point of view of discriminative measurement of radiations of high SID in mixed fields.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our earlier studies [16] have shown that the TL response of the dosimetric peak at 200 "C in LiF TLD-100 is about 30 times more sensitive to thermal neutrons as compared to y-rays on a DE basis. Thus the PL from F t centers in TLD-100 will be nearly 45 times more efficient than that of TL of the 200 "C peak from the point of view of discriminative measurement of radiations of high SID in mixed fields.…”
Section: Discussionmentioning
confidence: 92%
“…a high y-dose of 1.45 x lo3 Gy and a relatively low thermal neutron fluence of about 10" n cm-2 give nearly the same PL emission. The thermal neutron fluence of 10" n cm-2 is equivalent to a dose equivalent (DE) of 1.07 Sv [16]. For y-rays, 1 Sv 2 1 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CaSO 4 :Dy or Tm, impurity concentrations in the range 0.05-0.2 mol% were found to be optimum for TL (Ayyangar et al 1974, Nambi et al 1974, Prokic 1978, Atone et al 1993b. While studying redox reactions and RPL in CaSO 4 :Eu, similar concentrations have been used in previous studies (Bapat 1977, Calvert and Danby 1984, Upadeo et al 1994.…”
Section: Incorporation Of Eumentioning
confidence: 88%
“…codopant shows the maximum TSL sensitivity. At concentrations higher than 0.2 mol%, the TSL intensities were reduced due to concentration quenching [10,11]. About a 45% increase in the TSL efficiency is seen in Zn and Cd (each 0.…”
Section: Methodsmentioning
confidence: 98%